Analysis of frost visualization over a fin and tube heat exchanger by natural convection. Issue 1 (2nd January 2019) - Amini, Mohammad; Yaghoubi, Mahmood; Pishevar, Ahmad R.
ABSTRACT: In this article, studies are made on frost formation and flow over a fin and tube heat exchanger due to natural convection for various conditions of relative humidity, air ambient temperature, and mean refrigerant temperature. The results include frost deposition, steps of frost formation, and its effect on heat transfer rate for different conditions. The results show that frost is formed only on the tip of the fins with higher thickness from top to bottom due to small distance between the fins. Frost causes to trap the air which increases the thermal resistance and reduces heat transfer in the system.